2020
DOI: 10.3390/medicina56110617
|View full text |Cite
|
Sign up to set email alerts
|

Successful Embolization of Posterior Inferior Pancreaticoduodenal Artery Pseudoaneurysm on the Grounds of Chronic Pancreatitis—Case Report and Literature Review

Abstract: Pancreatic pseudoaneurysm is a rare but life-threatening clinical entity. In this paper, we present a case of a 74-year-old man, who was admitted to our clinic with a diagnosis of an acute on chronic pancreatitis complicated by walled-off-pancreatic-necrosis, with subsequent development of peripancreatic pseudoaneurysm. After initial conservative management, the patient recovered and was discharged from the hospital. However, he soon returned feeling anxious due to a pulsatile abdominal mass. Abdominal Color–D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…Modern interventional radiology provides minimally invasive endovascular treatment, which is increasingly used because of improved technical capabilities and low morbidity rates. 29 Angioembolization offers exceptional diagnostic and therapeutic possibilities for the precise identification and localization of the pseudoaneurysm. Additionally, exclusion of the blood vessel responsible for pseudoaneurysm formation from circulation can be achieved by stenting or embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern interventional radiology provides minimally invasive endovascular treatment, which is increasingly used because of improved technical capabilities and low morbidity rates. 29 Angioembolization offers exceptional diagnostic and therapeutic possibilities for the precise identification and localization of the pseudoaneurysm. Additionally, exclusion of the blood vessel responsible for pseudoaneurysm formation from circulation can be achieved by stenting or embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exclusion of the blood vessel responsible for pseudoaneurysm formation from circulation can be achieved by stenting or embolization. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…9 Mitrovic et al showed the endoscopic coil embolisation of posterior IPDA by a technique called "sandwich technique". 10 In our case report we present to you, the pseudoaneurysm of the posterior IPDA with the metallic coiling by interventional radiology team once the hemodynamic stabilisation was achieved within 72 hours.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, localizing the blood vessels surrounding a cyst is of great importance to confirm the optimal puncture site for EUS-guided drainage. Color Doppler can also be used to avoid vascular structures if needed[ 8 ].…”
Section: Discussionmentioning
confidence: 99%